Vegetation analysis and the effectiveness of methyl metsulfuron herbicide to control weeds in immature oil palm plantation - Asma Pani; Ardi; Siska Efendi (Faculty of Agriculture, Tompotika Luwuk University, 2022)
One of the obstacles faced in oil palm cultivation, especially in the immature plant phase, is weeds, weeds can inhibit oil palm growth. So that weeds require special attention during cultivation, the presence of these weeds will become competitors for oil palm plants in fulfilling nutrients, light and water. This study aims to determine the composition of the types and vegetation structure of weeds in immature oil palm plants in large plantations so that the dose of herbicide with active ingredient Methyl Metsulfuron 20% is effective in controlling weeds in immature oil palm plantations in large plantations and studying the phytotoxicity of herbicides made from 20% active Methyl Metsulfuron in immature oil palm trees in large plantations. This study used a randomized block design (RBD), which consisted of 7 levels of treatment, 5 of which used the herbicide methyl metsulfuron 20% at a dose of 87.50 g / ha, 75.00 g / ha, 62.50 g / ha, 50.00 g / ha, 37.50 g / ha. ha and 2 including mechanical and control weeding which is repeated 4 times. Data analysis was performed with the F test, followed by the DMRT test at 5% level. The results showed that there were two species of weeds that dominated the research area, namely B. mutica and A. gangetica weeds with SDR values of 33.13% and 24.73%. The application of herbicides made from 20% methyl metsulfuron as active ingredients in controlling weeds in immature oil palm plantations is able to control 2 types of weeds, namely weeds including Melastoma malabathricum, Clidemia hirta with the best dose of 50.00 g / ha and 37.50 g / ha from the first 4 weeks up to 12 Weeks After Application (MSA).